MICRO AND MACRO AGGREGATION OF SOILS OF THE KONIMEKH NATURAL GEOGRAPHICAL REGION (Scientific journal of the Fergana State University, 2025)
The article presents scientific data on micro- and macro-aggregation of soils distributed in the Konimekh natural geographical region. According to the general analysis, when looking along the profile of the studied soils, in the main cases from the top to the bottom layers, “very poor” (>60%), “unsatisfactory” (40-60%), “satisfactory” (25-40%), “good” (15-25%) and “very good” (